Les terres cuites des Salines de Kition : étude d’un culte chypriote d’époque classique - Pauline Maillard (Les Carnets de l’ACoSt)
The so-called “Salines sanctuary” was established close to old Kition, modern Larnaka, on the south coast of Cyprus. This place of worship, of which no traces have survived, was located outside the city walls and directly adjacent to a large salt lake. On those shores were found around 600 terracotta figurines, all dated from the sixth to the fourth century B.C.E. They mainly represent women, or goddesses, capped with high kalathoi. Produced in local workshops, those figurines are very close in iconography to contemporary Greek products. Nevertheless, they reveal the fine, local “tour de mains” of Kitian coroplasts. The use of specific processes, combining moulding and modelling, reveals the strong attachment of local workshops to Cypriot coroplastic techniques, as well as their adaptability to local cults and divinities, in the context of a cosmopolitan Cypro-Phoenician city.